Acceptability and feasibility of shared medical appointments to support self-management of anxiety and depression in primary care in England: a qualitative study of service user/patient perspectives - Fiona Graham; Mei Yee Tang; Megan Hanrahan (BMJ Open)
Objective Shared medical appointments (SMAs) are an innovative care delivery method that provides delivery of clinical care while also supporting self-management. Their usefulness for mental health conditions has only briefly been explored, though early evidence demonstrates their utility for supporting mental health management. Therefore, this study set out to better understand the views that adults with anxiety and depression have towards SMAs as a way of receiving care to support self-management in primary care.Design and methods A qualitative study using 1:1 semi-structured interviews which were analysed thematically following Braun and Clarke’s six-phase reiterative process. We employed a deductive, theory-informed approach to thematically analyse the data.Participants The final sample consisted of 17 predominantly White ethnic adults with a clinical diagnosis of anxiety and/or depression from five different regions in England. Participants represented a broad age group (22–74 years) and a range of socioeconomic backgrounds.Results Three main themes were established: (1) motivation to attend an SMA, (2) barriers and challenges to SMA engagement and (3) implementation preferences. The concept of SMAs was largely acceptable to participants, although participants reported several factors that would influence their decision to attend an SMA. Participants held some reservations but were on the whole receptive to the idea. The main benefits reported were peer support, support for self-management and quicker access to care. Drawbacks reported included risks to patient confidentiality, negative impact on emotional well-being and the unsuitability of the group setting for some patients. Some salient preferences identified included face-to-face/hybrid delivery formatting and mental health specialist involvement.Conclusions SMAs in primary care to support anxiety and depression self-management would be acceptable to patients, contingent on the mode of delivery of the SMAs. Future acceptability research should explore SMA appropriateness for diverse patient populations of different ethnic backgrounds, to inform their potential wider roll-out in English primary care.